Towards Building Semantic Next Generation Network: A Preliminary Study. - Toh, Kidd S.C; S.M.F.D, Syed Mustapha (2011)
Next Generation Network has drawn great attention by the researchers and telecommunication industries as the future generation in the communication technologies and services. The interest covers all aspects on NGN from the global standards, architecture and services. The management of services provided in the NGN environment has posed great challenges due to the heterogeneity of the service protocols, service requirements and specifications and service functionalities. The recent effort in the autonomics of service management is the initial effort towards achieving this paper. The paper proposes enhancement of the automated service management through embedding the semantic service descriptions that can be referenced to the service ontology for service creation and management. IMS (IP Multimedia System) is used as the core communication platform as it provides various services running on different protocols besides the common internet protocols and web services.